What Does Routinely Collected Pooled DIALOG, PROM and PREM Data Tell Us? - Akshith Shetty; Stuart Spicer; Rahul Bhattacharya (BJPsych Open)
Aims: The DIALOG scale has been implemented as a routine patient outcome and experience measure (PROM/PREM) in East London Foundation Trust (EL FT). We used large routinely collected DIALOG data to assess impact of treatment across different domains of life and whether the impact of treatment changed with Community Mental Health Transformation CMH (NHS Long Term Plan). We also carried out secondary disaggregation analysis of pooled data based on protected characteristics interrogating through an equity lens.